THE ROLE OF MAGNESIUM SUPPLEMENTS ON HYPERTENSION IN PREGNANCY AND PREECLAMPSIA - Raissa Nurwany; Shafira Fitri Ramadhina; Pariyana Pariyana (Andalas Obstetrics And Gynecology Journal, 2024)
Objective:This article aims to discuss the effects of magnesium supplementation on clinicaloutcomes of pregnancy and highlights the benefits of magnesium supplementation in reducing therisk of hypertension in pregnancy and preeclampsia. Method: In this systematic review article, theauthor conducted a literature search using certain keywords and selected articles that were publishedfrom 2013-2023, can be accessed in full-text in pdf format, and are in Indonesian or English. Themethods used were in accordance with the reporting guidelines provided in the Preferred ReportingItems for Systematic Review and Meta-Analysis Protocols (PRISMA-P). Results: After carefullysearching the database and eliminating articles that were not related to the topic, 6 articles wereobtained for review. Hypertension in pregnancy and preeclampsia are serious health problems thatcan harm both mother and baby. Magnesium supplements have been studied as a way to reduce therisk of hypertension in pregnancy and preeclampsia. Conclusion: Magnesium supplements may helpreduce the risk of hypertension in pregnancy and preeclampsia.